Work Motivation, Compensation, and Work Environment for Part Time Student Job Satisfaction with Gender as a Control Variable - Ferawati, Laeli; Kadarningsih, Ana (International Journal of Economics, Management and Accounting, 2024)
This research aims to see whether work motivation, compensation, and work motivation have an influence on employee satisfaction. The objects of this research are students who are working part-time in Semarang. Data collection was carried out by literature study and distributing questionnaires to 16 universities in Semarang with 138 respondents getting answers. The data analysis methods used in this research include descriptive analysis, normality test, heteroscedasticity test, multiple linear regression analysis, and coefficient of determination test (R²). The device or application used to analyze data in this research is SPSS version 26 software. The results of this research show that the work motivation variable does not have a significant influence on employee satisfaction, the compensation variable shows a significant positive influence on employee satisfaction, and the work environment variable also shows a significant and positive influence on employee satisfaction.